2002
DOI: 10.1002/cjce.5450800507
|View full text |Cite
|
Sign up to set email alerts
|

Gas—Liquid Mass Transfer Coefficient in Stirred Tank Reactors

Abstract: Volumetric gas—liquid mass transfer coefficient (kLa) data available in the literature for larger tanks (T = 0.39 m to 2.7 m) have been analyzed on the basis of relative dispersion parameter, N/Ncd. It was observed that at a given superficial gas velocity (VG), kLa values were approximately the same irrespective of geometric configuration (size of the tank, type and size of the impellers, type of the sparger, etc.) at a particular N/Ncd. A single correlation based on N/Ncd is presented which shows satisfactory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 18 publications
5
37
0
Order By: Relevance
“…This power reduction is due to the formation of cavities behind the impeller blades and the different density of the fluid under gassed and ungassed conditions (van't Riet and Smith, 1973). The effect of aeration has been extensively studied by Nienow et al (1977), Oosterhuis and Kossen (1981), Warmoeskerken and Smith (1981) and Yawalkar et al (2002) for a single impeller system as studied here. It has been shown that the gassed power input is usually 30-40% of the ungassed power input depending on the type of impeller and aeration rates used (Oosterhuis and Kossen, 1985).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…This power reduction is due to the formation of cavities behind the impeller blades and the different density of the fluid under gassed and ungassed conditions (van't Riet and Smith, 1973). The effect of aeration has been extensively studied by Nienow et al (1977), Oosterhuis and Kossen (1981), Warmoeskerken and Smith (1981) and Yawalkar et al (2002) for a single impeller system as studied here. It has been shown that the gassed power input is usually 30-40% of the ungassed power input depending on the type of impeller and aeration rates used (Oosterhuis and Kossen, 1985).…”
Section: Resultsmentioning
confidence: 94%
“…In Figure 4 N CD is represented by the minimum P g /P ug values in each data set. The flow pattern at this operating condition is characterized by a fully dispersed bubbled regime throughout the fluid without any flooding of the impeller (Yawalkar et al, 2002). At this point however the gas hold up is not sufficient to promote gross recirculation of bubbles throughout the dispersion.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The power consumption in ungassed systems is always higher than the power consumption in gassed systems, since aeration significantly influences the power drawn from the impeller by the fluid. 7 The effect of aeration has been studied extensively by Nienow et al, 91 Oosterhuis and Kossen, 92 Yawalkar et al 93 and Gogate et al 46 It has been shown that the gassed power input is usually 30-40% of the ungassed power input, …”
Section: Scale-up Based On Volumetric Power Consumptionmentioning
confidence: 99%